Mycobacterium avium in a shower linked to pulmonary disease - Falkinham, Joseph O.; Iseman, Michael D.; de Haas, Petra; van Soolingen, Dick (Journal of water and health, 2008)
Mycobacterium avium was isolated from hot and cold water samples and from sediment (biofilm) collected from the showerhead in the home of a woman with M. avium pulmonary disease lacking known M. avium risk factors. IS1245/IS1311 DNA fingerprinting demonstrated that M. avium isolates from the hot and cold water and showerhead sediment demonstrated a clonal relationship with the patient's M. avium isolate. The data provide evidence that showers may serve as sources of infection by waterborne M. avium.